DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP LANSIA DI POSYANDU KEMUNING PUSKOPKAR BATU AJI - Suprihatin, Ratih; Mona, Silvia (Universitas Batam, 2020)
Susenas 2017 data shows that almost 10% of the elderly live alone so they need support from the surrounding environment considering that their lives are more at risk. Family support itself is a form of interpersonal relationship that protects a person from the effects of bad stress so that it has an impact on the quality of his life. The initial survey found that 5 elderly people said that they lacked support from their families to accompany them in care when they were sick, sometimes they felt sad because their families were busy with work and busy with their new families. This study aims to determine the closeness of family support to the quality of life of the elderly. This research method is cross sectional with descriptive analytic design. Research site at Posyandu Kemuning Puskopkar Batu Aji. The population in this study were the elderly who visited the posyandu, the sampling technique used was total sampling. The time of the study was in March - July 2019, the research instrument used a questionnaire. Data analysis using chi_square statistical test. The results showed that 69.1% of respondents had good family support, 67.3% of respondents had a good quality of life and 84.2% of respondents who received good family support so had a good quality of life, these results indicate that there is a relationship between family support with the quality of life of the elderly, with a p-value of 0.000 (<0.05). In conclusion, there is a significant relationship between family support and the quality of life of the elderly at the Posyandu Kemuning Puskopkar Batu aji Batam City in 2019. Suggestions from the results of this study are that it is hoped that families will always increase their support for the elderly by paying attention to the health development of the elderly, improving family communication with the elderly, and trying to fulfill their needs. all the needs needed by the elderly as well as for the puskesmas and posyandu to be able to involve the family in every activity at the posyandu.